A4 Development of disease modifying therapies in Huntington's disease. Issue 10 (7th September 2012) - Bates, G
Abstract : Dr Gillian Bates is Professor of Neurogenetics and Head of the Division of Genetics and Molecular Medicine at King's College London School of Medicine. Her research interests are focused on understanding the molecular pathogenesis of Huntington's disease (HD) and the development of therapeutic interventions. Her basic science projects include the proteolytic processing of huntingtin; huntingtin aggregation; chaperones, the heat shock response and impairment of protein homeostasis in HD. She uses a combination of pharmacology and genetic manipulation to validate therapeutic targets in mouse models of HD. She has been elected to the Royal Society (2007), EMBO (2002) and the Academy of Medical Sciences (1999). Huntington's disease (HD) is a devastating neurodegenerative disorder for which there are no disease-modifying treatments. Since the Identification of the mutation as a CAG repeat expansion in 1993, a wide range of single cell (yeast and mammalian cell culture), invertebrate ( Drosophila melanogaster ) and Caenorhabditis elegans ) and mammalian (mouse and rat) models have been developed to better understand disease pathogenesis and identify targets for disease modification and allowed is a protein folding disease caused by a CAG/polyglutamine expansion in the huntingtin protein (HTT) and we are employing genetic and pharmacological approaches to evaluate mechanisms by which protein homeostasis might be restored.